Assessing Language Laboratory Facilities’ Usage, Benefits, and Challenges among Open and Distance Learners in Nigerian Universities - Fatimayin, Foluke Florence; Owolabi, Josiah; Osikomaya, Mojisola Olufunke; Bello, Lukuman Kolapo (West African Journal of Open and Flexible Learning, 2024)
This study assessed language laboratory facilities’ usage, benefits, and challenges in the teaching and learning of languages in ODL institutions in Nigeria using a mixed-methods design. ODL stakeholders in single and dual-mode Nigerian universities formed the population of the study. The sample was selected using a multi-stage sampling technique. Three major instruments that were validated by experts in languages and measurement and evaluation of the Faculty of Education, National Open University of Nigeria, and had high positive reliability coefficients were used for data collection. They are: ODL students’ usage of language laboratory facilities for learning (r = 0.950), Perceived benefits of usage of language laboratory facilities among ODL learners in Nigerian universities (r = 0.972), and the interview schedule for ODL language facilitators in the selected universities. Three research questions and two hypotheses guided the study. Frequency counts, percentages, mean, standard deviation, ANOVA, and thematic analysis were used to analyse the data collected. Results showed that respondents use the facilities in one way or another other but not always. More than half of the respondents agreed that the language laboratory facilities highlighted are beneficial for teaching and learning languages in Nigerian ODL institutions. Some of the challenges highlighted include the inability of the institutions to provide power-generating systems and adequate language laboratory facilities. Based on the findings, it was recommended that funding institutions, especially language departments, should be improved upon and acquire more language laboratory facilities to increase usage and benefits derived by learners and facilitators. Résumé : Cette étude a évalué l’utilisation, les avantages et les défis des laboratoires de langues dans l’enseignement et l’apprentissage des langues dans les institutions d’apprentissage des langues au Nigeria à l’aide d’une conception à méthodes mixtes. Les parties prenantes de l’ODL dans les universités nigérianes monomodes et bimodes ont constitué la population de l’étude. L’échantillon a été sélectionné à l’aide d’une technique d’échantillonnage à plusieurs degrés. Trois instruments principaux qui ont été validés par des experts en langues et en mesure et évaluation de la Faculté d’éducation de l’Université nationale ouverte du Nigeria, et qui présentaient des coefficients de fiabilité positifs élevés, ont été utilisés pour la collecte de données. Ils sont ; L’utilisation des laboratoires de langues par les étudiants pour l’apprentissage (r = 0,950), les avantages perçus de l’utilisation des installations de laboratoire de langue parmi les apprenants en ODL dans les universités nigérianes. (r = 0,972) et le calendrier des entretiens pour les facilitateurs de langue en ODL dans les universités sélectionnées. Trois questions de recherche et deux hypothèses ont guidé l’étude. Les données recueillies ont été utilisées pour analyser les données recueillies, les pourcentages, la moyenne, l’écart-type, l’ANOVA et l’analyse thématique. Les résultats ont montré que les répondants utilisent les installations d’une manière ou d’une autre, mais pas toujours. Plus de la moitié des personnes interrogées ont convenu que les installations de laboratoire de langues mises en évidence sont bénéfiques pour l’enseignement et l’apprentissage des langues dans les institutions nigérianes d’apprentissage et de débauche. Parmi les défis mis en évidence, citons l’incapacité des institutions à fournir des systèmes de production d’énergie et des laboratoires de langues adéquats. Sur la base des résultats, il a été recommandé que les institutions de financement, en particulier les départements de langues, soient améliorées et acquièrent davantage d’installations de laboratoire de langues afin d’accroître l’utilisation et les avantages retirés par les apprenants et les animateurs. Mots-clés : Laboratoires de langues, Apprentissage ouvert et à distance, Utilisation, Avantages, Défis